Research on College English Listening and Speaking Teaching Based on Production-oriented Approach - Yan, Hu (Journal of Educational Research and Policies, 2025)
The production-oriented approach regards motivating, enabling and assessing as important stages in the teaching process, closely integrating input and output, and emphasizing the integration of learning and application. This paper first analyzes the current situation of college English listening and speaking teaching, then gives a brief overview of the production-oriented approach, and finally takes the Unit 6 “For every question there is an answer” of “New Horizon College English Viewing, Listening, and Speaking (Book 3, the Fourth Edition)” as an example to illustrate the design of English listening and speaking teaching under the guidance of the production-oriented approach, so as to improve the teaching effect of college English listening and speaking courses through the teaching method combining learning and application.